(Quick)Silver Masters: Modern and Post-Modern Revivals of Quattrocento Chivalric Poems. (3rd April 2019) - Giammei, Alessandro
ABSTRACT: Modern revivals of the 'golden' age of Italian chivalric epic are widely studied. This essay addresses the less explored legacy of fifteenth-century chivalric poems, traditionally regarded as 'silver' models of the genre in terms of language, structural harmony and literary ambition. After profiling a more general Quattrocentismo in early twentieth-century art and literature, I consider two specific cases: Alberto Savinio's creative uses and intentional misuses of the Morgante maggiore, and Alfredo Panzini's neo-classical revivals of the Orlando innamorato. Savinio works on fifteenth-century epic as an archaeologist, Panzini as a restorer. By analyzing the importance of Pulci and Boiardo as ethic and aesthetic models for such apparently opposing intellectuals (a protagonist of international vanguardism and a fascist erudite author of popular novels), I move to define the Quattrocento masters as 'quicksilver' rather than 'silver' auctoritates. I conclude by showing their continuing influence beyond the end of modernism.